Metacognitions as a predictor of problematic social media use and internet gaming disorder: Development and psychometric properties of the Metacognitions about Social Media Use Scale (MSMUS). (February 2023) - Akbari, Mehdi; Hossein Bahadori, Mohammad; Khanbabaei, Salar; Boruki Milan, Bahman; Horvath, Zsolt; Griffiths, Mark D.; Demetrovics, Zsolt
Highlights: The Metacognitions about Social Media Use Scale (MSMUS) is a newly developed scale. The MSMUS can optimally assess social media metacognitions (SMMCs). The MSMUS has a two-factor structure (negative metacognitions and positive metacognitions). SMMCs had significant moderate correlations with problematic social media use (PSMU). SMMCs had predictive effects on the presence of PSMU with and without gaming disorder. Abstract: The aim of the present study was to investigate social media use metacognitions through the development of a new scale, the Metacognitions about Social Media Use Scale (MSMUS). In addition, the study included measures of problematic social media use (PSMU), gaming metacognitions, and gaming disorder (GD) to test concurrent validity. A total of 2390 Iranian adolescents (835 males and 1555 females) aged between 13 and 18 years (M = 16.01 years, SD = 1.38) participated in a cross-sectional online survey. The results of the exploratory factor analysis (n = 1195) and confirmatory factor analysis (n = 1195) suggested that the MSMUS (i) can optimally assess metacognitions concerning social media, and (ii) has a two-factor structure ("negative metacognitions about social media" and "positive metacognitions about social media"). The scale was found to be measurement invariant among males and females, and among individuals with and without risk for PSMU. Social media metacognitions presented significant and predominantly (i) moderate correlations with PSMU symptom severity, and (ii) weak correlations with GD symptom severity. Furthermore, positive and negative social media metacognitions had significant and positive predictive effects on the presence of risk for PSMU with and without a risk for GD – even over the effects of age, gender, and gaming metacognitions. This finding may indicate that metacognitions are possibly a transdiagnostic variable which might be helpful in developmentally assessing addictive behaviors, especially negative metacognitions which might be a risk factor for co-occurring addictive behaviors.